NILAI-NILAI EDUKATIF DALAM GEGURITAN ARJUNA PREMADA - NI WAYAN MARIASEH (Universitas Mahasaraswati K. Mataram, 2024)
This research is aimed to explore educative values in geguritan Arjuna Premada. The problems in this research is explore educative values structure in geguritan Arjuna Premada and analyze educative values structure inter relations of geguritan Arjuna Premada. While the purpose of this research is acquaint literature opus such as geguritan deeply as a Hindu Bali local wisdom and to understanding educative values that is contained in geguritan Arjuna Premada also to understanding inter relations of educative values structure in geguritan Arjuna Premada. Data of this research is obtained by documentation and bibliography method and also support by interview method as a base reconstruct researcher’s view (as cosidered decision) in analysis. Then that data are interpreted by giving sense, explain the pattern and characteristic between inter various concept. To acquire that pattern and characteristic are supported by structural fungtional theory, semiotika theory and some another theory that is related with this research. Based on analysis result, conceusion obtain that: educative values structure in geguritan Arjuna Premada is devisible on three category that is a) Cognitive values consist of symbolic value and curiosity value (include else opus curiosity). b) Affective values consist on two category that is social attitude values and spiritual attitude values.. c) While psychomotorist values is divisible on skills and ability in use something to creating/producing. Inter relations of educative values structure in geguritan Arjuna Premada can be described similar a tree. Cognitive values are similar as tree’s roots that is absorb substances in soil to bring tree’s sustain. Affective values are similar as stalk tree’s that is buttress the leaves and branches; and Psychomotorist values are similar as leaves of the tree. Whereas unity values, work values, humanity, symbolic value, curiosity, religious values, skills and ability in use something are similar as branches of the tree.